Sosialisasi Pengurusan PT dan Edukasi Ekspor di Yayasan Sumatra Volunteer Jorong Balai Labuah Bawah, Kabupaten Tanah Datar - Winny Alna Marlina; Nur Ari Sufiawan (Warta Pengabdian Andalas, 2022)
The Sumatra Volunteer Foundation is a non-profit organization in which the Foundation's main activity is a handicraft business whose main raw materials are obtained from nature. Creative businesses from bamboo produced by Sumatra Volunteers need socialization of management Ltd which aims to potentially gain greater profits because of the wider product market share besides that it can also preserve regional cultural values through foreign markets, so it is necessary to disseminate education on export foreign trade activities as his supporters. The methods used include lectures, discussions, and business consulting. This activity is expected to help handicraft businesses and creative business products from bamboo Sumatra Volunteer Foundation and the establishment of an Ltd which is strengthened by signing at a Notary.